Chemical Characteristics of High PM Episodes Occurring in Spring 2014, Seoul, Korea. (15th February 2016) - Shin, Hye Jung; Park, Seung-Myung; Park, Jong Sung; Song, In Ho; Hong, You Deog
Abstract : This study was conducted for understanding of characteristics of two different high PM episodes occurred during the spring of 2014 in Seoul, Korea. Case 1 was the phenomenon by complex of long range transport and following domestic stagnation. Case 2 was caused by the Asian dust event. During high PM episodes, atmospheric condition became more acidic. The equivalent concentration ratio of nitrate to sulfate decreased to 0.75 and 0.95 in Case 1 and Case 2, respectively, implying that sulfate concentration increase was greater than nitrate concentration increase in high PM episode possibly caused by long range transport. In high PM episodes, SOR and NOR increased with steeper rate for NOR. Considering correlation between temperature and SOR, it was suggested that the homogeneous formation of sulfate was not active in the Korean Peninsula, especially in high PM episodic periods. On the other hand, heterogeneous sulfate formation reaction was dominant for high PM episodes. Considering NOR and its correlation with temperature and humidity, it was suggested that NO2 oxidation was mainly caused by homogeneous oxidation in Case 1. For Case 2, heterogeneous oxidation mainly contributed to forming the nitrate due to the extremely high particle concentrations in Asian dust.